Winter is not forever eaudiobook Seasons of the heart (oke) series, book 3. - Oke, Janette (Seasons of the Heart, 2003)
Internationally best-selling inspirational author Janette Oke is beloved for her novels of faith. Winter Is Not Forever is the continuation of the touching Seasons of the Heart saga begun in Once Upon a Summer (K1041) and continued in The Winds of Autumn (K1052). Featuring a folksy narration by Johnny Heller, this tale of a young man ready to graduate from high school and begin his adult life is touching and poignant.